The Effect of Low Methoxyl Pectin and Sugar Concentration on Characteristics of Coconut (Cocos nucifera L.) Jam - Melanie Cornelia; Ivana Ivana; Djohan Sofia; Candra Yulius Tahya (University of Sultan Ageng Tirtayasa, 2024)
Coconut is one of many kinds of fruit that grow in Indonesia. Coconut is well known as a nutritional and beneficial fruit, especially for health. Many consumers like coconut because it’s delicious, cheap, and consists of many vitamins and minerals. The application of coconut on food product such as jam was suitable because freshly opened coconut with presence of oxygen became very easily damaged and usually contaminated by spoilage microorganism. Coconut jam was made by gelling agent low methoxyl pectin. Gelling properties in low methoxyl pectin are dependent on concentration low methoxyl pectin and sugar, so the effect concentration of low methoxyl pectin and the concentration of sugar were investigated. The concentration of low methoxyl pectin (0%, 0.5%, 1%, and 1.5%) and the concentration of sugar (0%, 10%, 20%, and 30%) were used in this research. And the result of this research could be concluded that increasing concentration of low methoxyl pectin and sugar, increased viscosity and consistency and decreased syneresis, whiteness, and aw of coconut jam. The best jam formulation choosen was formulation with addition of 1 % of low methoxyl pectin and 20 % of sugar.